STUDI KASUS PEMANFAATAN POJOK LITERASI PRAKTIK DEAR DI SMPN 5 KEPANJEN - Ifa Novita; Luluk Sri Agus Prastyoningsih (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
This study aims to examine school efforts in instilling a culture of literacy and practice of DEAR (Drop Everything And Read) at SMPN 5 Kepanjen with critical reading skills, the benefits obtained from the literacy corner in class, the obstacles in practicing DEAR (Drop Everything And Read) and the utilization of the corner literacy that has not had an impact on students in SMP Negeri 5 Kepanjen classes and solutions to related obstacles in optimizing the use of class literacy corners at SMP Negeri 5 Kepanjen. This qualitative research uses a phenomenological type. The research informants involved all school members, namely students, teachers and the principal of SMPN 5 Kepanjen. The results of the study show that the school is trying to instill a culture of DEAR (Drop Everything And Read), which must be done every day by students at SMP Negeri 5 Kepanjen. By habituating students to visit literacy corners, creating literacy activity programs, applying critical reading skill and trying to bring in publishers to offer a wide selection of reading books to students to be used in literacy corners as literacy materials. The reading corner functions to create a new classroom atmosphere, can also be used as a place for casual reading, fosters student creativity and can be used as a place to channel hobbies. In addition, students enjoy reading under the guidance of the teacher, because they can learn and share ideas and experiences while learning. The obstacle to optimizing the function of the literacy corner is the low introduction of a reading culture, the solution to optimizing the function of the literacy corner is that the teacher participates in providing books to be read by students, adapts to the needs of students in class and tries to complete a collection of various readings, so that when students read they do not seem boring. When they are in the literacy corner, carrying out DEAR (Drop Everything And Read) activities can create critical thinking so that they finally like reading activities.